Evaluation of a mobile phone based agro-advisory programme on sunflower (Helianthus annuus L.): EVALUATION OF A MOBILE PHONE BASED AGRO-ADVISORY PROGRAMME ON SUNFLOWER - G D S KUMAR,; M PADMAIAH,; K ALIVELU, (Journal of Oilseeds Research, 2014)
The increasing penetration of mobile phone networks and handsets in India presents an opportunity to make useful information on agriculture more widely available to farmers. The present study was conducted with 240 farmers growing sunflower (Helianthus annuus L.) in two districts in Andhra Pradesh State, India during 2011-12. The taluks and villages were selected based on highest area under sunflower and the presence of farmers with IKSL (IFFCO Kisan Sanchar Limited) sim cards. The farmers were selected by random sampling method. The study used ex-post facto and pre- and post- experimental research designs. An improvised Bennett's hierarchy, a logic model was used for evaluation. The results indicated significant differences in knowledge and adoption scores of pre- and post-dissemination groups indicating the impact of the system. Mobile phones based advisories can create awareness and make knowledge accessible to farmers and to some extent mobilize communities to adopt best practices. To further improve knowledge, adoption of improved practices and impart required skills to farmers training sessions and demonstrations need to be organized after the broadcast of advisories.